Resistance training in humans and mechanical overload in rodents do not elevate muscle protein lactylation - Mattingly, Madison L.; Ruple, Bradley A.; Sexton, Casey L.; Godwin, Joshua S.; McIntosh, Mason C.; Smith, Morgan A.; Plotkin, Daniel L.; Michel, J. Max; Anglin, Derick A.; Kontos, Nicholas J.; Fei, Shengyi; Phillips, Stuart M.; et al. (Frontiers in Physiology, 2023)
Although several reports have hypothesized that exercise may increase skeletal muscle protein lactylation, empirical evidence in humans is lacking. Thus, we adopted a multi-faceted approach to examine if acute and subchronic resistance training (RT) altered skeletal muscle protein lactylation levels. In mice, we also sought to examine if surgical ablation-induced plantaris hypertrophy coincided with increases in muscle protein lactylation. To examine acute responses, participants' blood lactate concentrations were assessed before, during, and after eight sets of an exhaustive lower body RT bout (n=10 trained college-aged men). Vastus lateralis biopsies were also taken before, 3-h post, and 6-h post-exercise to assess muscle protein lactylation. To identify training responses, another cohort of trained college-aged men (n=14) partook in six weeks of lower-body RT (3x/week) and biopsies were obtained before and following the intervention. Five-month-old C57BL/6 mice were subjected to 10 days of plantaris overload (OV, n=8) or served as age-matched sham surgery controls (Sham, n=8). Although acute resistance training significantly increased blood lactate responses 7.2-fold (p<0.001), cytoplasmic and nuclear protein lactylation levels were not significantly altered at the postexercise time points, and no putative lactylation-dependent mRNA was altered following exercise. Six weeks of RT did not alter cytoplasmic protein lactylation (p=0.800) despite significantly increasing VL muscle size (+3.5%, p=0.037), and again, no putative lactylationdependent mRNA was significantly affected by training. Plantaris muscles were larger in OV versus Sham mice (+43.7%, p<0.001). However, cytoplasmic protein lactylation was similar between groups (p=0.369), and nuclear protein lactylation was significantly lower in OV versus Sham mice (p<0.001). The current null findings, along with other recent null findings in the literature, challenge the thesis that lactate has an appreciable role in promoting skeletal muscle hypertrophy.